‘The third person in the room’: Recording the counselling interview for the purpose of counsellor training – barrier to relationship building or effective tool for professional development? - Gossman, Marion; Miller, Judi H. (Counselling & Psychotherapy Research, 2012)
Objective: Audio and videotape interview recording for training and supervision in counsellor education is commonplace within New Zealand, yet researchers have paid little attention to its value perceived by students. This study explores counselling students’ perceptions of the effects of recording counselling interviews on themselves, their clients and on the counselling process. Design: Counselling students from five tertiary educational settings in New Zealand participated in individual or focus group interviews to discuss their experiences of recording counselling interviews. Findings: All interviewees indicated that recording initially curtailed their ability to be completely present in the counselling interview. Some thought this may have negatively influenced their clients’ ability to use the counselling session effectively. Most noted their own increased confidence over time. Almost all considered recording to be extremely beneficial to the development of effective counselling skills. Conclusion: Most students considered the benefits of recording to outweigh the drawbacks. Implications for continuing the practice of recording and playing back interviews in counsellor-education programmes are considered.